From childhood trauma to hyperarousal in adults: The mediating effect of maladaptive shame coping and insomnia - Schalkwijk, Frans; Van Someren, Eus J. W.; Nicolai, Nelleke J.; Uijttewaal, Julia L.; Wassing, Rick (Frontiers in Human Neuroscience, 2023)
A new line of insomnia research focuses on the developmental trajectories from early live stress to insomnia in adulthood. Adverse childhood experiences (ACE’s) might create a vulnerability for later maladaptive coping with distress, as seen in chronic hyperarousal or insomnia. In an fMRI study, failure to dissociate the neurobiological components of shame from autobiographical shameful memories in insomnia was reflected by continued activation of the dorsal anterior cingulate cortex (dACC), which may be a result of maladaptive coping in the wake of ACE’s. Following up on that study, the current pilot study explores the relation between ACE’s, shame coping-styles, adult insomnia, hyperarousal, and neurobiology of autobiographical memory. We used existing data (N = 57) from individuals with insomnia (N=27) and controls (N=30), and asked these participants to complete the childhood trauma questionnaire. Two structural equation models were used to test the hypotheses that shame-coping styles and insomnia symptom severity mediate the association between ACE’s and (1) self-rated hyperarousal symptoms and (2) dACC activation to recall of autobiographical memories. For the association between ACE’s and hyperarousal, there was a significant mediation of shame-coping style (p<0.05). This model also indicated worse shame coping with more ACE’s (p<0.05) and worse insomnia symptoms with more ACES’s (p<0.05), but no association between shame coping and insomnia symptoms (p=0.154). In contrast, dACC activation to recall of autobiographical memories could only be explained by its direct association with ACE’s (p<0.05), albeit that in this model more ACE’s were also associated with worse insomnia symptoms. These findings could have an implication for the approach of treatment for insomnia. It could be focused more on trauma and emotional processing instead of conventional sleep interventions. Future studies are recommended to investigate the relationship mechanism between childhood trauma and insomnia, with additional factors of attachment styles, personality and temperament.